CLAIMING SELF; THE ROLE OF AFRIKOLOGY IN SOCIAL TRANSFORMATION - Buntu, Baba A. O. (Scriptura, 2013)
A number of crises - including political, economic and philosophical crises - have become intrinsically associated with Africa. This article argues that the most alarming crisis might be located in a worldview where Africa’s self-determination has become absent. The challenge of repositioning Africa and deconstructing its ontological base represents an opposition to Academia, institutions and scholarship, where preconceived ideas of Africa as ‘the other’ have become dominant. To this effect, the need for reclaiming a collective sense of Self is deemed necessary as a premise for authentic change. The field of theology, with its focus on relations between woman/man, God and nature, needs to be challenged on this. By examining the role of African epistemology as integral to liberating strategies, the article advances Afrikology as a transdisciplinary and decolonial solution to social transformation.